Masculine Embodiment Among Sexual Minorities in a Women's Prison. Issue 2 (3rd April 2021) - Smoyer, Amy B.; Divita, David; Perrault, Allison
ABSTRACT: Sexual minority women are disproportionately incarcerated and more likely to experience structural and interpersonal violence while incarcerated than heterosexual cisgender women. To build knowledge about this population and inform social work practice, theories of embodiment were used to conduct thematic analysis of five interviews with lesbian, gay, bisexual, transgender, and queer masculine-identified people who had been incarcerated in a women's prison. This analysis explicates how participants used bodily practices to construct gender and communicate identity to themselves and others. Uniforms, prison regulations, and physical manifestations of female embodiment complicated these efforts. Participants described the ways in which they monitored and evaluated their own bodies while also managing the constant surveillance of their bodies by others. Taken together, these findings explicate the ways in which participants' bodies were produced both through their actions and the external gaze of others. Implications for social work include exploration of language and masculinity in practice settings and suggestions for correctional policies. Findings encourage inclusion of non-binary frameworks and increased attention to the embodied self in order to expand understandings of human behaviour in the social environment. IMPLICATIONS: Interpret with caution any information about gender identity surmised from intake forms and observation of clients' bodily practices. Ask clients to describe their gender identity. Prioritise correctional policies that promote the health and safety of incarcerated people and staff over policies that enforce social norms related to gender and have no implications on security. Encourage re-entry service providers to collaborate with LGBTIQA+ organisations that provide social support to clients who identify as sexual minorities.